Influence of traditional and non-traditional entries on figure skating jumps - Nevius, B. L.; Russell, P. J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The choice of performing jumps from traditional entries or nontraditional entries are left to the discretion of the skater. The purpose of this study was to examine the influence of non-traditional entries on the kinematics of two figure skating jumps using a simple quantitative tool available to coaches. It was hypotheisized that non-tradional entries would alter jump kinematics. Ten skilled figure skaters were videotaped while performing toe loops or salchows with both traditional and non-tradional entires. Kinematic variables were determined with Dartfish. Results indicated that non-traditional entries had significantly more jump height and ankle plantar flexion at landing in the toe loop, and signifcantly more horizontal displacment in the salchow. Coaches may wish to examine these subtlies to determine a skater`s readiness to practice non-traditional entries.